Validation of the Portuguese self-administered computerised 24-hour dietary recall among second-, third- and fourth-grade children - Carvalho, M.A. (2015)
Background: Current methods for assessing children's dietary intake, such as interviewer-administered 24-h dietary recall (24-h DR), are time consuming and resource intensive. Self-administered instruments offer a low-cost diet assessment method for use with children. The present study assessed the validity of the Portuguese self-administered, computerised, 24-h DR (PAC24) against the observation of school lunch. Methods: Forty-one, 7–10-year-old children from two elementary schools, in Lisbon, were observed during school lunch followed by completion of the PAC24 the next day. Accuracy for reporting items was measured in terms of matches, intrusions and omissions; accuracy for reporting amounts was measured in terms of arithmetic and absolute differences for matches and amounts for omissions and intrusions; and accuracy for reporting items and amounts combined was measured in terms of total inaccuracy. The ratio of the estimated weight of food consumed with the actual weight consumed was calculated along with the limits of agreement using the method of Bland and Altman. Results: Comparison of PAC24 against observations at the food level resulted in values of 67.0% for matches, 11.5% for intrusions and 21.5% for omissions. The mean for total inaccuracy was 3.44 servings. For amounts, accuracy was high for matches (−0.17 and 0.23 servings for arithmetic and absolute differences, respectively) and lower for omissions (0.61 servings) and intrusions (0.55 servings). PAC24 was found to under-estimate the weight of food on average by 32% of actual intake. Conclusions: PAC24 is a lower-burden procedure for both respondents and researchers and, with slight modification, comprises a promising method for assessing diet among children.